Matched analysis of induction chemotherapy plus chemoradiotherapy versus induction chemotherapy plus radiotherapy alone in locoregionally advanced nasopharyngeal carcinoma: a multicenter study - Zhang, Bin (Oncotarget, 2016)
BACKGROUND: The relative efficacy of induction chemotherapy (IC) followed by concurrent chemoradiotherapy (CCRT) versus IC followed by radiotherapy (RT) alone in locoregionally advanced NPC remains unclear. METHODS: A total of 877 patients with locally advanced NPC who underwent IC/CCRT or IC/RT at four institutions in China between January 2004 and December 2010 were retrospectively assessed. IC was cisplatin-based combination chemotherapy; concurrent chemotherapy, single agent cisplatin. Two-dimensional conventional radiotherapy (2DCRT) was the radiotherapy technique. All patients were matched in an equal ratio using a pair-matched method. Overall survival (OS), disease-free survival (DFS), distant metastasis-free survival (DMFS), locoregional relapse-free survival (LRRFS) and toxicities were assessed. RESULTS: Eligible patients were matched (n = 642; 321 patients per arm) based on eight clinicopathological characteristics. Five-year OS, DFS, DMFS, and LRRFS were 76%, 70%, 86%, and 88% for IC/CCRT and 75%, 70%, 90%, and 91% for IC/RT, respectively. There were no statistically significant survival differences between arms (P>0.05), even in subgroup analysis. In multivariate analysis, treatment (IC/CCRT vs. IC/RT) was not an independent prognostic factor for any survival end-point. Grade 3/4 acute gastrointestinal toxicities (vomiting, nausea) and hematological toxicities (leucopenia/neutropenia, thrombocytopenia and anemia) were significantly more common in the IC/CCRT arm than IC/RT arm during RT. CONCLUSION: Overall, IC/CCRT failed to demonstrate any survival advantage but higher acute toxicities over IC/RT in locoregionally advanced NPC.